2019
DOI: 10.1080/0886022x.2019.1603110
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity Troponin-I levels in asymptomatic hemodialysis patients

Abstract: Reduction in renal clearance and removal by hemodialysis adversely affect the level and utility of high-sensitivity troponin I (hsTnI) for diagnosis of acute myocardial infarction (AMI) in hemodialysis (HD) patients. Furthermore, HD process itself might cause undesirable myocardial injury and enhance post HD hsTnI levels. This comparative cross-sectional study was conducted to compare the hsTnI levels between 100 asymptomatic HD patients and their 107 matched non-chronic kidney disease (CKD) population. The hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…One study showed that the normal range of serum hs-cTnT in patients with CKD is higher than that in patients without CKD (139 ng/L in patients with CKD versus 14 ng/L in patients without CKD) [23]. Another study revealed that the baseline hs-cTnT levels in asymptomatic hemodialysis patients were higher than non-CKD patients (54.3 versus 18 ng/L) [24]. Receiver operating characteristic curves of high-sensitivity cardiac troponin-T (TnT) levels on admission, and dynamic changes in these levels for the diagnosis of acute myocardial infarction (diagnosis based on coronary angiography or cardiac echocardiography) (A) for patients with eGFR < 60 mL/min/1.73 m 2 , (B) patients with eGFR > 60 mL/min/1.73 m 2 , (C) patients with chronic kidney disease (CKD) history, and (D) patients without CKD history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that the normal range of serum hs-cTnT in patients with CKD is higher than that in patients without CKD (139 ng/L in patients with CKD versus 14 ng/L in patients without CKD) [23]. Another study revealed that the baseline hs-cTnT levels in asymptomatic hemodialysis patients were higher than non-CKD patients (54.3 versus 18 ng/L) [24]. Receiver operating characteristic curves of high-sensitivity cardiac troponin-T (TnT) levels on admission, and dynamic changes in these levels for the diagnosis of acute myocardial infarction (diagnosis based on coronary angiography or cardiac echocardiography) (A) for patients with eGFR < 60 mL/min/1.73 m 2 , (B) patients with eGFR > 60 mL/min/1.73 m 2 , (C) patients with chronic kidney disease (CKD) history, and (D) patients without CKD history.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that the normal range of serum hs-cTnT in patients with CKD is higher than that in patients without CKD (139 ng/L in patients with CKD versus 14 ng/L in patients without CKD) [ 23 ]. Another study revealed that the baseline hs-cTnT levels in asymptomatic hemodialysis patients were higher than non-CKD patients (54.3 versus 18 ng/L) [ 24 ]. Nevertheless, the Fourth Universal Definition of myocardial infarction used the same value of hs-cTnT for the diagnosis of AMI in patients either with reduced or normal eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of 5 th generation hs-cTn, non-ischaemic troponin elevation above the reference threshold, now termed 'myocardial injury', is commonly seen in patients with CKD; affecting up to 75% of dialysis patient (Gunsolus et al, 2018;Miller-Hodges et al, 2018;Sandoval et al, 2017;Sarkisian et al, 2016;Shah et al, 2018;Tarapan et al, 2019). Numerous studies have suggested that myocardial injury is now the most common cause of troponin elevation and confers a poor prognosis independent of the underlying mechanism of its elevation (Chew et al, 2014;McFalls et al, 2011;Miller-Hodges et al, 2018;Tarapan et al, 2019).…”
Section: Myocardial Injury and Potential Myocardial Therapiesmentioning
confidence: 99%
“…Tarapan et al. [1] research results are very meaningful. The association between Hb and hsTnI in MHD patients is complicated and urgently needs more studies to confirm.…”
mentioning
confidence: 99%
“…After careful reading through the article called ‘High sensitivity Troponin-I levels in asymptomatic hemodialysis patients’ by Tarapan et al. [1]. Cardiac troponin-I is a well-known crucial parameter in diagnosis of acute myocardial infarction (AMI).…”
mentioning
confidence: 99%